Learning experiences for the transition to professional work - Leigh N. Wood; Jim Psaros; Erica French; Jennifer W.M. Lai; Tahir Nisar (Cogent Business & Management, 2015)
A better educated workforce contributes to a more informed and tolerant society with higher economic output, and this is also associated with higher levels of personal health, interpersonal trust and civic and social engagement. Against this backdrop, the role of universities has expanded, as university learning has moved beyond providing an education to preparing students for leadership positions within society. This article examines the effectiveness of final-year learning experiences from the perception of recent graduates. The aim is to improve undergraduate curriculum to facilitate the transition to professional employment. An online quantitative and qualitative survey instrument was developed to investigate graduates' perceptions of their different learning experiences and assessment types in their senior year. Four hundred and twelve alumni from five universities completed the survey. Our results indicate that graduates value case studies, group work and oral presentations, and that graduates rate lectures and guest lectures from practitioners as the least important in their transition to work. The results validate the use of graduate capability frameworks and mapping the development of the skills over the curriculum. These results are useful for curriculum designers to assist with designing programmes on the transition to professional work.
Keywords: 650